Phosphorus and sulphates removal from wastewater using copper smelter slag washed with acid - Moatlhodi Wise Letshwenyo (Springer, 2021)
Abstract In this study, we present the performance of acid washed copper smelter slag for the adsorption of phosphates and sulphates from wastewater. The aim of the study was to investigate the removal of phosphates and sulphates from wastewater using acid washed copper smelter slag at batch scale by exploring influences of different variables. The leachate concentrations of copper, iron, manganese and lead released from the adsorbent were 1.8, 128.2, 0.32 and 0.20 mg L−1, respectively at pH 2. The point of zero charge was at pH 6.04, Pseudo-Second Order kinetic model described the adsorption process better with an R2 value of 0.99. The experimental maximum adsorption capacities for phosphates and sulphates were 0.51 and 0.24 mg g−1 media, respectively, and 0.96 mg P g−1 media at pH 12 and 0.39 mg g−1 media for sulphates at pH 2, respectively. The process was endothermic with temperature having insignificant impact during adsorption. The maximum adsorption capacities for thermodynamic study were 0.103 ± 0.09 and 0.046 ± 0.004 mg g−1 media respectively, for PO4 3− P and SO4 2− at 60 °C. This study showed that acid washed copper smelter slag has an improved adsorption capacity for phosphate and sulphate ions but further investigations should be conducted to find ways of further improving the adsorbent performance. Article highlights There is increase in the adsorption capacity of acid washed copper smelter slag. The adsorption capacity of phosphorus is high at pH 12 and for sulphate at pH 6. The adsorption of phosphate and sulphate ions onto acid washed slag is an endothermic process. Intraparticle diffusion was not the only rate controlling mechanisms.